Educational technology in physical education learning: A bibliometric analysis using Scopus database - Perdima, Feby Elra; Suwarni, Suwarni; Gazali, Novri (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of the present study was to conduct a bibliometric analysis of the journal articles published in Scopus database on educational technology in physical education learning. In accordance with the objectives of this study, a systematic search was carried out in the Scopus database, which included high-quality scientific literature in more than 250 disciplines, including social sciences, and humanities. “Technology and Physical Education", followed by “Education" and "School" were the primary search terms used for the identification of studies and several health based databases were searched in English language literature in the Scopus database from 1999-2021. A total of 131 journal articles were published in the Scopus database within the time line of 1999-2021. A very low amount of literature was available relevant to technology and physical education within the timeframe of 1999 to 2009. Based on publications in the Scopus database, the findings revealed that: 1) The number of publications has increased, although there was an up-and-down trend from year to year. 2) Most of the publications were written by researchers located in several countries and universities. 3) “Structure and content of the educational technology of managing students’ healthy lifestyle” written by Alexander & Vladislav (2015) was the most cited article with 46 citations. 4) Universidad de La Sabana, Colombia, was found to be the most productive institution with 5 publications. 5) The keyword with the highest number of occurrences (19) in the research sample was “educational technology selection”.